COVID-19 incidence and outcomes among patients with kidney replacement therapy - Siribha Changsirikulchai; Pornpen Sangthawan; Jirayut Janma; Songyos Rajborirug; Thammasin Ingviya (Kidney Research and Clinical Practice, 2023)
Background We aimed to investigate the incidence, fatality, and associated factors in patients with hemodialysis (HD), peritoneal dialysis (PD), and kidney transplantation (KT) hospitalized for coronavirus disease 2019 (COVID-19) infection and reimbursed from the National Health Security Office (NHSO). Methods The retrospective cohort analysis was conducted from an electronic-claimed database, and COVID-19 vaccination status was evaluated in patients with HD, PD, and KT from January 2020 to December 2021. There were 85,305 patients reimbursed for HD, PD, and KT by the NHSO. The rates of COVID-19 infection, COVID-19 vaccination, comorbidities, fatalities, and the cost of treatment were evaluated. Results COVID-19 infection was observed in 1,799 of 36,982 HD cases (4.9%), 1,531 of 45,453 PD cases (3.4%), and 95 of 2,870 KT cases (3.3%). Patients receiving COVID-19 vaccinations were most common in the KT group, followed by those with HD and PD (76.93% vs. 70.65% vs. 51.34%, respectively). KT patients had a lower fatality rate compared to those with PD and HD (8.42% vs. 18.41% vs. 21.40%, respectively). Advanced age, diabetes, cardiovascular diseases, and COVID-19 vaccination status were associated with fatality. The adjusted odds ratios of fatality after receiving one or two doses of vaccines were 0.7 (95% confidence interval [CI], 0.6–0.9) and 0.3 (95% CI, 0.2–0.4), respectively. The cost of treatment was highest in patients with HD, followed by PD and KT. Conclusion The incidence of COVID-19 infection was higher in patients with HD than in those with PD or KT. COVID-19 vaccination following the national health policy should be encouraged for these patients to prevent fatality.